Can adolescents' subjective wellbeing facilitate their pro-environmental consumption behaviors? Empirical study based on 15-year-old students - Min Zhang; Weidong Zhang; Yong Shi (Frontiers Media S.A., 2023)
PurposeTo address the challenge of declining pro-environmental behaviors in adolescence, this paper uses the theoretical foundations for subjective wellbeing to verify the influence of three latent dimensions of subjective wellbeing (life satisfaction, positive emotions, and negative emotions) on adolescents' pro-environmental consumption behaviors (PECBs). Furthermore, we explore the moderating effects of nations and regions in the relationship between subjective wellbeing and PECBs in adolescents.MethodBased on the international data from the Programme for International Student Assessment 2018 (PISA 2018), we construct a unique dataset that includes 57,182 samples related to the subjective wellbeing and PECBs of 15-year-old students from eight countries/economies. Specially, we employ an ordered probit model to test our hypotheses.FindingsBoth adolescents' life satisfaction and positive emotions can significantly improve their PECBs, while there is a significant negative association between negative emotions and PECBs. At the nation's level, adolescents' life satisfaction and negative emotions in developed countries/economies significantly impact PECBs. In contrast, the positive emotions of adolescents in developing countries/economies have more substantial effects on PECBs. At the regional level, the impact of all three dimensions of adolescents' subjective wellbeing on PECBs is more significant in rural than urban areas.Originality/valueThis paper provides a new perspective for understanding adolescents' PECBs from the insights of subjective wellbeing. Previous studies have examined the effects of life satisfaction or happiness on PECBs in adults. This paper examines the impact of subjective wellbeing on adolescents' PECBs from life satisfaction, positive emotions, and negative emotions, which suggests that promoting adolescents' subjective wellbeing can be an effective strategy for encouraging PECBs. From a comparative research perspective, we further analyze the differences between the nations at different levels of development, the rural and urban areas, providing a valuable reference for policymakers and practitioners in promoting pro-environmental behaviors among adolescents.